Model of Environmental Education with Integration of Life Cycle Assessment in term of Recycling Behavior - Donkonchum, Sirikanya; Thiengkamol, Nongnapas; Thiengkamol, Chatchai (Mediterranean Journal of Social Sciences, 2012)
The objective of this research was to develop a model of environmental education with integration of Life Cycle Assessment (LCA) in term of recycling behavior. Moreover, understating on LCA in term of recycling behavior. Populations were 37,156 undergraduate students of academic year 2012 of Mahasarakham University. Simple random sampling was employed to select the sample. Questionnaire was used as instrument for data collecting. Pearson correlation and Path Analysis were used for data analysis. The results revealed that psychological traits in terms of goal of life (GL) showed directly affected to inspiration in aspects of role model (RM) with .554, It also showed directly affected to LCA in term of recycling behavior (RC) and energy consumption behavior (EB) with .604 and .598 while RM showed directly affected to RC and EB with .621 and .565. Moreover, psychological states in terms of religion belief (RB) showed directly affected to RM with .631 and it also directly affected to RC and EB with 622 and .601. Considering on environmental education integration with LCA in term of recycling behavior, in aspect of environmental attitude (AT) showed directly affected to RM with .611 and it showed also directly affected IE with .632 and directly affected to RC and EB with .629 and 605. EB showed directly affected to RC with .522.